Adjunctive loading dose of cilostazol in preventing periprocedural myocardial infarction. Issue 4 (August 2016) - Xu, Ling‐Xia; Chen, Kang‐Yin; Liu, Tong; Zheng, Xin‐Tian; Jiao, Zhan‐Quan; Xu, Yanmin; Li, Guangping
Summary: Introduction: Periprocedural myocardial infarction (PMI) is a common complication of percutaneous coronary intervention (PCI). This study evaluated the safety and efficacy of adjunctive loading dose of cilostazol in preventing PMI in patients with acute coronary syndrome (ACS). Methods: A total of 113 patients with ACS undergoing PCI were randomized to receive loading doses of dual (aspirin plus clopidogrel; DAPT group; n=57) or triple antiplatelet therapy (aspirin plus clopidogrel plus cilostazol; TAPT group; n=56). The loading and maintenance doses were 100 and 50 mg bid for cilostazol. Patients in the TAPT group received adjunctive cilostazol for 1 week. Cardiac biomarkers were measured before PCI, 8 and 24 hours after PCI to determine the incidence of PMI. Results: There was no significant difference in the incidence of PMI between the TAPT and DAPT groups (32.1% vs 47.4%, P =.098). However, in the antiplatelet‐naïve subgroup, TAPT significantly lowered the incidence of PMI compared to DAPT (17.9% vs 42.9%, P =.042). In the antiplatelet‐treated subgroup, the incidences of PMI were comparable (46.4% vs 51.7%, P =.698). Multivariable logistic analysis showed that antiplatelet‐treated (vs antiplatelet‐naïve) (hazard ratio [HR]: 2.45; 95% confidence interval [CI]: 1.09–5.52; P =.030) subgroup was independently associated with PMI. However, TAPT (vs DAPT) (HR: 0.51; 95% CI: 0.23–1.14; P =.102) was not an independent protective factor of PMI. Conclusions: The present single‐center, randomized study indicates that TAPT with adjunctive cilostazol was not associated with lower incidence of PCI‐related PMI in patients with ACS. Further study with large study population is needed to get definite conclusions.